SAS 9 study guide : - Hezaveh, Ali (Wiley, 2007)
SAS® 9 Study Guide is designed to help users of SAS® 9 become familiar with the fine points of the software as well as develop solid study strategies that will shorten preparation time and ensure successful exam results. The following five study topics are addressed with a focused chapter devoted to each: accessing data; creating data structures; managing data; generating reports; and handling errors. SAS® 9 Study Guide provides both a conceptual and practical approach to each of these areas with detailed explanations followed by examples.